A comparision study of rotorcraft with Hybrid Electric Propulsion System - Lee, D.; Kang, S.; Yee, K. (My University, 2019)
Hybrid Electric Propulsion System (HEPS) is being developed as a novel propulsion system not only for the reduction of carbon emission but also for significant design freedom. However, the inevitable disadvantages of additional weight penalty and efficiency lost were induced by the electrification. Despite this, various aero-propulsive interactions enabled by the design freedom were proposed to overcome these impediments for enhanced performance of the aerial vehicle. Therefore, this study presents a comparative study of winged helicopter and fan-in-body, the two exemplary hybrid concepts of rotorcraft and fixed-wing, utilizing HEPS to investigate novel rotorcraft concepts capable of maximizing advantageous characteristics of the electrification. To this end, HEPS rotorcraft design framework was proposed, integrating the sizing of electrical devices and the aero-propulsive interaction. With the HEPS rotorcraft design framework, the design optimizations were carried out for two different mission profiles; resupply mission dominated by high-speed maneuver and reconnaissance mission dominated by the hovering and loitering missions. The success of this study presents that hybridization of the propulsion system incurs notable performance refinements for the mission requiring the maximum power with short operating time, mainly due to the inherent technological limitation of the battery.